Discourse from the Perspective of Mohammed Arkoun: An Examination of the Values of Interfaith Dialogue - Imronudin Imronudin; Riza Muhammad (Institut Agama Islam Negeri (IAIN) Manado, 2023)
Interfaith dialogue is presented to appreciate the truth in others and work together to realize actual problems, such as citizenship rights, violence, ignorance, poverty, equality, injustice, social inequality, and so on. Arkoun's influence with the post-structuralist reveals the critical urgency of religious teachings in shaping the integrity of society. So, in Arkoun's thought, every interpretation is not sacred and must be done with a sociocultural approach that is contextual and open to criticism. He sought to deconstruct Islamic thought, which was considered sacred and closed, using the social sciences approach to represent a humanist, rational, and loving dialogue. This research method uses critical analysis methods with Paul Ricoeur's hermeneutic approach in reading sources about Mohammed Arkoun. The results of this research are the development of contemporary Islamic thought by Arkoun by presenting Islam as Epistemology, including producing interreligious dialogue as a tool to create tolerance, prioritize dialogue, and establish a brotherhood.